Ein provinzialrömischer Kultplatz auf der Gradišče bei Sankt Egyden in Unterkärnten - Hinker, Christoph (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
The publication focuses on a small cave near St. Egyden in Carinthia (Austria), where archaeological excavations were carried out in 2011. The scientific evaluation of the archaeological data has shown that the place was a Roman-era cult site, which is characterized by remains of offerings and celebrations and meals held by a small rural community. In the present publication, this archaeological source material is made accessible in detail in order to discuss questions of cult practice, the deity that may has been worshipped, and the organization and composition of the cult community.